2022
DOI: 10.1021/acs.langmuir.2c02610
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Responsive Phenol Formaldehyde Resin: Changes of Interface Energy on the Aggregation Process

Abstract: Phenol formaldehyde resins (PFRs) as a colloidal oil displacement agent were commonly used to plug pores in crude oil reservoirs for enhanced oil recovery (EOR). The aggregation–dispersion and charging behavior of PFR may affect the rheology and plugging performance of the suspension. To understand the aggregation–dispersion and charge of PFR, turbidity, dynamic light scattering, and electrophoretic light scattering experiments were carried out at pH = 10 with different concentrations of salt solutions (NaCl, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The stability of colloid mainly depends on aggregation stability. Our previous PFR research found that [7][8][9][10][11][12][13] , its stability and aggregation morphology mainly depend on the long-range Van der Waals force and the electrostatic repulsion force between colloidal particles. Speci cally, the fractal dimension [14] was calculated by the double slope method to predict the morphological and structural changes of the aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of colloid mainly depends on aggregation stability. Our previous PFR research found that [7][8][9][10][11][12][13] , its stability and aggregation morphology mainly depend on the long-range Van der Waals force and the electrostatic repulsion force between colloidal particles. Speci cally, the fractal dimension [14] was calculated by the double slope method to predict the morphological and structural changes of the aggregates.…”
Section: Introductionmentioning
confidence: 99%